Comparative federalism : states' rights and national power - McWhinney, Edward, 1924- (Heritage, 2019)
In contrast to the views current only a few years ago, when federalism as a system of government was regarded, in academic circles in North America at least, as passe and even reactionary, there is today throughout the world, and especially in Western Europe, a tremendous interest in the federal idea. It is seen as a dynamic, even revolutionary idea, and it has been seized on as the best institutional device available for assisting and promoting the integration of the Western European countries - one which offers, moreover, the best opportunities for preserving liberal, pluralistic ideals in an era of strong centralized governments. The interest in federalism and in supranational integration makes essential a definitive study of the working practice of federal law and government in those societies where federalism has been long in operation.-